Viability and Biochemical Content Changes in Seed Storage of Jabon Putih (Anthocephalus Cadamba (Roxb) Miq.) - Naning Yuniarti; Nurhasybi Nurhasybi (Institut Pertanian Bogor (IPB University), 2015)
Seed deterioration is the process of deteriorated seed in view of viability that changed the physiological and chemical content. The aim of this research is to find out the effect of moisture content and storage on viability and biochemical content of jabon putih seed. Completely Randomized Design was used for decreasing moisture content based on seed drying time for 0, 24, 48, 72, 96, 120 hours, and Completely Randomized Factorial Design was used for the combination of moisture content (drying time for 0, 24, 48, 72, 96, 120 hours) and room storage (ambient room, air-conditioned room, refrigerator). The results of this research are: (1) seed drying time and seed storage affected the change of seed viability and biochemical content, (2) seed drying time and seed storage influence significantly the value of moisture content, germination percentage, and biochemical content (lipid, carbohydrate, protein), (3) The longer time of seed drying and seed storage has decreased the seed moisture content, germination percentage, and the carbohydrate content, but it has increased the content of lipid and protein, and (4) the seeds were stored in refrigerator has better viability compared to dry cold storage and ambient room.